Formulasi Sediaan Krim Ekstrak Etanol Kulit Buah Sawo (Manilkara Zapota L.) dan Uji Efektivitas Sebagai Pelembab Kulit - Hamna, Aulia; Safriana, Safriana; Fatimah, Cut; Tanjung, Siti Aisyah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The skin is the largest organ of the body that is often exposed to the environment so it is prone to dryness and health problems. Skin moisturizing cosmetic preparations often contain synthetic chemicals so that their use often causes side effects, in the form of skin disorders so that it is necessary to find alternative natural ingredients that can provide safer skin moisture, for example ripe sapodilla fruit skin, which has been empirically proven to moisturize the skin. This study aims to test the chemical content, formulate ethanol extract of ripe sapodilla fruit skin in the form of a cream, and evaluate the effectiveness and safety of the cream as a skin moisturizer. The method used in this study is an experimental method with a quantitative approach, starting with the manufacture of simplicia and its characteristics test, manufacture of ethanol extract of ripe sapodilla fruit skin, phytochemical screening test, making cream preparations with ethanol extract concentrations of ripe sapodilla fruit skin 5%, 10%, and 15% followed by physical quality tests including organoleptic and stability tests, homogeneity tests, emulsion type tests, pH tests, spreadability tests, adhesion tests, irritation tests on volunteers, preference tests, and effectiveness tests of the preparation as a skin moisturizer. The results of the study showed that phytochemical screening of fresh ripe sapodilla fruit skin, crude drugs, and its ethanol extract showed the presence of alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids, and glycosides. Ethanol extract of ripe sapodilla fruit skin can be formulated into a skin moisturizer cream preparation with stable color, aroma, and shape within 4 weeks, the pH of the preparation is in accordance with the skin pH of 4.5-6.5, does not irritate and has effectiveness as a skin moisturizer, increases water content in the skin by 40.04 ± 3.47%. and reduces oil content by 24.46 ± 2.20%.